Aleksandra Kostić Tmušić: Poetic Elements in Serbian Hagiographic Literature, Faculty of Philosophy Kosovska Mitrovica, 2017 - Nektarios Lois, Georgios (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
The article does not contain abstract.